Atypical radiological aspect of meningioma: Web-like enhancement - Mohammed Al amine El farissi, MD; Mohamed Dahamou, MD; Najia Bakkar, MD; Youness Dehenh, MD; Mohamed Khoulali, PhD; Noureddine Oulali, PhD; Faycal Moufid, PhD (Radiology Case Reports, 2023)
Meningiomas are the most common extra-axial neoplasmof the central nervous system (CNS). There are a number of characteristic imaging features of meningiomas on magnetic resonance imaging (MRI) that allow an accurate diagnosis, however there are a number of atypical features that may be diagnostically challenging. Furthermore, a number of other neoplastic and non-neoplastic conditions may mimic meningiomas. This case highlights the importance of careful analysis of imaging findings and the need for consideration of all possible diagnoses, including rare or atypical presentations of common neoplasms such as meningiomas. Early detection and accurate diagnosis are crucial in determining the appropriate management and improving the outcomes for patients with intracranial tumors.